Feeling good, approaching the positive - Kobrock, Kristina; Solzbacher, Johannes; Gotzner, Nicole; König, Peter (Frontiers in Psychology, 2024)
Approach and avoidance behaviors have been extensively studied in cognitive science as a fundamental aspect of human motivation and decision-making. The Approach-Avoidance Bias (AAB) refers to the tendency to approach positive stimuli faster than negative stimuli and to avoid negative stimuli faster than positive ones. Affect and arousal in involved individuals are assumed to play a crucial role in the AAB but many questions in that regard remain open. With this in mind, the present study aimed to examine the impact of positive and negative mood on the AAB. To achieve this goal, we conducted an experiment where participants watched either positive or negative videos prior to performing an approach-avoidance task. We have not been able to confirm our preregistered hypothesis that mood induction moderates the AAB. Instead, our results suggest that an AAB can be robustly shown after both the positive and the negative intervention. Positive Affect Negative Affect Schedule (PANAS) results show that the participants' affective state was influenced by the mood intervention only in the form of increased emotional intensity. Participants did not self-report a change in mood valence that corresponds to the valence of the video primes. However, the behavioral data shows that after watching a positive video, participants are faster in approaching positive stimuli than negative stimuli. At the same time, we do not find a similar effect after the negative intervention. These findings suggest that positive and negative affect might play an important role in shaping the AAB that is modulated by stimulus valence. This provides new potential insights into the underlying mechanisms of human motivation and decision-making. Specifically, we argue for potential differences between attention and reaction toward a valenced stimulus.